Laparoscopic appendectomy in a second trimester pregnant patient due to acute appendicitis: a case report - Estudillo, Gamaliel Vázquez; Viveros, Edwin Y.; Vidales, Rodrigo Nuñez; Salazar, Ivanhoe Larracilla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Acute appendicitis is the most frequent surgical procedure of general surgery during pregnancy, which occurs in 0.04 to 0.2% of all pregnancies; this represents 25% of non-obstetric operations performed during pregnancy. A 33-year-old female patient with a second-trimester pregnancy, which goes to the Emergency Department for abdominal pain, when performing the anamnesis and physical examination, the suggestive picture of acute appendicitis is integrated, for which additional laboratory and cabinet studies are carried out, according to the clinical suspicion it is decided to perform diagnostic laparoscopy and management according to findings; cecal erythematosus appendix is evident, so appendectomy is performed, finding proximal appendicolitis. Later with good evolution and satisfactory exit for the binomial. This procedure has been associated with shorter surgery times, shorter hospital stays and fewer complications compared to open surgery.